2018
DOI: 10.1002/prp2.406
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselectivity in the tissue distribution of perhexiline contributes to different effects on hepatic histology and peripheral neural function in rats

Abstract: Perhexiline, a chiral drug, is a potent antiischemic agent whose clinical utility is limited by hepatic and neural toxicities. It inhibits mitochondrial carnitine palmitoyltransferase‐1, however, excessive inhibition predisposes toward tissue steatosis. This pilot study investigated the distribution of the two enantiomers and their toxicological potential. Dark Agouti rats (n = 4 per group) were administered vehicle or 200 mg/kg daily of racemic, (+)− or (−)‐perhexiline maleate orally for 8 weeks. Plasma bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…These IC50 ranges are similar to the recommended maximum therapeutic plasma concentration of perhexiline of around 2 µmol/L [21]. Small animal studies have demonstrated that perhexiline concentrates further within tissues [26]. Thus, there are anti-tumour effects when the plasma concentration is within the therapeutic range.…”
Section: Perhexiline Anti-cancer Studies and Proposed Mechanismssupporting
confidence: 73%
See 1 more Smart Citation
“…These IC50 ranges are similar to the recommended maximum therapeutic plasma concentration of perhexiline of around 2 µmol/L [21]. Small animal studies have demonstrated that perhexiline concentrates further within tissues [26]. Thus, there are anti-tumour effects when the plasma concentration is within the therapeutic range.…”
Section: Perhexiline Anti-cancer Studies and Proposed Mechanismssupporting
confidence: 73%
“…Adjunctive use of perhexiline may increase the inhibition of biological target of interest and result in enhanced overall anti-cancer efficacy. The observation in animal studies that perhexiline concentrates within visceral organs [26] and crosses the blood-brain barrier [34] further makes this drug a favourable cancer therapeutic candidate. It may be a particular benefit for tumours in the central nervous system where the blood-brain barrier, by restricting the effective delivery of many cancer drugs, makes treatment of primary brain cancer and central nervous system metastasis challenging [97].…”
Section: Clinical Feasibility Of Perhexiline As An Anti-cancer Agentmentioning
confidence: 99%
“…It can be avoided by careful monitoring of perhexiline plasma concentrations and adjusting dosing to keep plasma concentrations below 0.6 mg/L (equivalent to ~2 µM) [ 5 , 19 , 32 , 33 ]. Compared to plasma, in vivo perhexiline tissue concentrations are markedly higher, as demonstrated in the livers and hearts of rats and humans [ 34 , 35 , 36 ]. Tumour clearance studies show that a daily oral regimen of up to 7 mg/kg (~10 µM) perhexiline for 4 weeks was well tolerated in mice and produced significant reduction in tumour sizes for different tumour types [ 12 , 20 , 22 , 37 ].…”
Section: Discussionmentioning
confidence: 99%